Influence of solid cohesion on viscous properties in Norton law for aluminum alloys during partial solidification - Nagata, Yoshihiro (Elsevier Science SA, 2022)
This study investigated the influence of the solid cohesion, f(sc), on the viscous properties (m-value and k-value in the Norton law) for aluminum alloys during partial solidification. In the previous study of Haaften (Mater. Sci. Eng. A, 336 (2002), 1-6), a constitutive model taking into account f(sc) was proposed as (epsilon)over dot = k(T) (sigma/f(sc)(theta,T))(n(=1/m)), where theta referred to the dihedral angle at the solid/liquid interface. However, even though it is well known that the m-value decreases with the decreasing temperature in the semi-solid state, the model defined the m-value as a constant to the temperature. Therefore, m = f(f(sc)) and k = g(f(sc)) during solidification were clarified in this study. The viscous properties were obtained by tensile tests during partial solidification for Al-5mass%Mg and Al-2mass %Cu alloys. As a result, it was found that the change in the m-value of 0 <= f(sc) < f(sc vertical bar eut.st) was expressed by the following linear rule-of-mixtures: m = m(solid)(f(sc)/f(sc vertical bar eut.st)) + m(liquid)(1-f(sc)/f(sc vertical bar eut.st)), where f(sc vertical bar eut.st) is f(sc) at the beginning of the eutectic solidification, while m(solid) and m(liquid) are the m-values just below the solidus temperature and at f(sc) = 0, respectively. The increase in f(sc) due to the eutectic solidification hardly affected the change in the m-value and such a value was equivalent to m(solid). On the contrary, the change in the k-values was found to obey the Arrhenius equation rather than be controlled by f(sc). It is suggested that regardless of the aluminum alloy composition, the viscous properties of partial solidification can be determined using the these relationships.